DISTINCTIVE FEATURES OF ISLAMIC ARCHITECTURE (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
Islamic architecture is renowned for its rich cultural and artistic heritage, reflecting the diverse range of Islamic civilizations throughout history. This article aims to provide a comprehensive analysis of the distinctive features of Islamic architecture, highlighting its unique characteristics, spatial organization, and decorative elements.